2022
DOI: 10.1007/s11904-022-00629-7
|View full text |Cite
|
Sign up to set email alerts
|

Transgender Individuals and Digital Health

Abstract: Purpose of review The goal of this review is to assess the use of digital technologies to promote the health and well-being of transgender and gender diverse (TGD) people. Recent findings TGD individuals experience numerous health disparities, including low uptake of HIV prevention strategies, such as pre-exposure prophylaxis, increased HIV incidence, and suboptimal HIV-related outcomes. These health disparities are the result of widespread intersectional stigma on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 87 publications
(58 reference statements)
1
5
0
Order By: Relevance
“…Participants described that peer support could be delivered in apps through the inclusion of chat rooms. Peer connections via e-health technologies have similarly been identified as an area of need among transgender people [ 52 ] and men from sexual minorities [ 53 ]. Peer support is available widely online, however participants described that including peer support forums within apps, such as chat rooms, could promote inclusivity and bridge the gap between LGBTQIA + peer support and cancer peer support.…”
Section: Discussionmentioning
confidence: 99%
“…Participants described that peer support could be delivered in apps through the inclusion of chat rooms. Peer connections via e-health technologies have similarly been identified as an area of need among transgender people [ 52 ] and men from sexual minorities [ 53 ]. Peer support is available widely online, however participants described that including peer support forums within apps, such as chat rooms, could promote inclusivity and bridge the gap between LGBTQIA + peer support and cancer peer support.…”
Section: Discussionmentioning
confidence: 99%
“…1) information delivered online on websites (e.g., World Health Organisation [WHO], 2022; Magee et al, 2012) or through online education programmes (e.g., Mustanski et al, 2015;Lacombe-Duncan et al, 2021); 2) advice and support online which may involve use of telecommunication such as video calls, live chats, email, or text services with charity or community-based organisation staff or peers (e.g., Radix et al, 2022;Skeen & Cain, 2022); and 3) clinical care provided online, such as STI/HIV self-sampling kits and test results (e.g., Bauermeister et al, 2015;Estcourt et al, 2017;Hottes et al, 2012;Ling et al, 2010;Brugha et al, 2011);PrEP (ePrEP;Kincaid et al, 2021); partner notification (PN) and testing options (e.g., Golden et al, 2022;Flowers et al, 2021;Mimiaga et al, 2008); and consultations (eConsult) and telemedicine (e.g., Sequeira et al, 2021;Lucas et al, 2023).…”
Section: A Potential Solutionmentioning
confidence: 99%
“…This will be inclusive of research into services and interventions. Services refer to digital GHC designed for LGBTQI+ youth for help-seeking, such as information, telecommunication, or clinical care (e.g., electronic consultation (e-consult); counselling; and access to hormone replacement therapy (HRT) (Radix et al, 2022). Interventions refer to digital strategies that have been developed to change a specific GH related behaviour or outcome for LGBTQI+ youth, such as education programmes, (e.g., to increase knowledge and understanding or decision making about GHC; Salvetti et al, 2022), including digital versions of services typically delivered in person (e.g., Shipherd et al, 2016;Blosnich et al, 2019).…”
Section: Ghcmentioning
confidence: 99%
“…Reported facilitators included being more engaged and having increased self-agency, whereas barriers included inconsistent access to the internet and smartphones. Radix et al [ 48 ] concluded that the use of health ITs (HITs) provides opportunities to improve the quality of care for TGD individuals. Not only can HIT solutions be designed to offer education and support addressing the social determinants of health, but the community also favors these solutions [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radix et al [ 48 ] concluded that the use of health ITs (HITs) provides opportunities to improve the quality of care for TGD individuals. Not only can HIT solutions be designed to offer education and support addressing the social determinants of health, but the community also favors these solutions [ 48 ].…”
Section: Introductionmentioning
confidence: 99%